FoMO (Fear of Missing Out) Among Youth Viewed From Herbert Marcuse’s Perspective: FoMO (Fear of Missing Out) Kalangan Muda Ditinjau dari Perspektif Herbert Marcuse - Siti Amallia (UIN Sunan Kalijaga Yogyakarta, 2022)
Following the trend seems to be a benchmark for teenagers in determining the extent of their level of association. To be recognized as slang teenagers, they are not infrequently willing to leave their identity. Excessive anxiety arises when he feels left behind with precious moments that are worldly. This condition is then associated with self-esteem and self-confidence, especially those involving peers. The focus of the study in this research is FoMO behavior(Fear of Missing Out) in adolescents reviewed fromHerbert Marcuse's perspective to find out the fundamental causes behind the anxiety experienced by adolescents due to social media. This research is (Library Research) using several sources such as books, journals and the internet. The methods used include descriptive, analytical, and interpretive methods to connect neo marxism theory with contemporary problems. From the results of the study, it was found that concerns about other people's judgments and good relations with their peers made teenagers lose their original self-identity. The emergence of anxiety that leads to an attitude of insecurity begins to appear when a teenager does not know himself as a whole. Generally, feelings of anxiety in adolescents are related to uploads on social media. Through his analysis, Herbert Marcuse, a neo marxism figure, sees the characteristics of a one-dimensional society that can be related to the FoMO phenomenon among teenagers, namely about false needs and images. Adolescents with FoMO tendencies have difficulty in interpreting themselves in substance. They mostly get stuck at the level of form and follow other people. The orientation of free human beings has deviated far from the order of life. So there needs to be a revolution of thought so that teenagers can better understand how to behave, not just follow trends . Keywords : FoMO, youth, social media, Herbert Marcuse, Marxism